2021
DOI: 10.1080/14756366.2021.1944127
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel benzofuran-isatin conjugates as potential antiproliferative agents with apoptosis inducing mechanism in Colon cancer

Abstract: In the current work, a new set of carbohydrazide linked benzofuran-isatin conjugates (5a-e and 7a-i) was designed and synthesised. The anticancer activity for compounds (5b-d, 7a, 7b, 7d and 7g) was measured against NCI-55 human cancer cell lines. Compound 5d was the most efficient, and thus subjected to the five-dose screen where it showed excellent broad activity against almost all tested cancer subpanels. Furthermore, all conjugates (5a-e and 7a-i) showed a good anti-proliferative activity towards colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…The search for new anticancer drugs requires potent inhibitory effects on cancer cell migration, invasion, and tumorigenesis. Thus, in this present study, after confirming the reported cytotoxic effect of the synthetic Compound 5a, a benzofuran-isatin conjugate, on colorectal adenocarcinoma HT29 and metastatic CRC SW620 cells (Eldehna et al, 2021c), we showed that Compound 5a exerted anticancer activities by inhibiting CRC cell proliferation, migration, invasion, and colony formation. Compound 5a also reversed epithelial-mesenchymal transition (EMT) phenotype markers by elevating E-cadherin expression and suppressing N-cadherin expression.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The search for new anticancer drugs requires potent inhibitory effects on cancer cell migration, invasion, and tumorigenesis. Thus, in this present study, after confirming the reported cytotoxic effect of the synthetic Compound 5a, a benzofuran-isatin conjugate, on colorectal adenocarcinoma HT29 and metastatic CRC SW620 cells (Eldehna et al, 2021c), we showed that Compound 5a exerted anticancer activities by inhibiting CRC cell proliferation, migration, invasion, and colony formation. Compound 5a also reversed epithelial-mesenchymal transition (EMT) phenotype markers by elevating E-cadherin expression and suppressing N-cadherin expression.…”
Section: Discussionsupporting
confidence: 89%
“…A complex process occurred in activating the extrinsic death receptor-dependent and intrinsic signaling pathways, and flow cytometry was applied for apoptosis determination and MtMP evaluation. Herein, after confirming the reported pro-apoptotic effect of Compound 5a, an increase in apoptotic cells was observed when both CRC cells were exposed to a higher concentration (20 μM) of Compound 5a (Eldehna et al, 2021c). At lower concentrations (5-10 μM), Compound 5a doubled (i.e., 10 vs. 5 μM) the percentage of apoptotic CRC cells, which aligned with Compound 5a-induced p53 upregulation, tumor suppressor protein well described to mediate apoptosis (Marei et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The anticancer test was conducted using the methods of the Drug Evaluation Branch, National Cancer Institute, Bethesda, MD, using 59 human tumour cell lines derived from nine human tissues. The GI 50 , TGI, and LC 50 dose-response parameters were calculated for each medication 37–39 .…”
Section: Methodsmentioning
confidence: 99%